Aortic root dimension changes during systole and diastole: evaluation with ECG-gated multidetector row computed tomography - de Heer, Linda M.; Budde, Ricardo P. J.; Mali, Willem P. Th. M.; de Vos, Alexander M.; van Herwerden, Lex A.; Kluin, Jolanda (International Journal of Cardiovascular Imaging, 2011)
Cardiac pulsatility and aortic compliance may result in aortic area and diameter changes throughout the cardiac cycle in the entire aorta. Until this moment these dynamic changes could never be established in the aortic root (aortic annulus, sinuses of Valsalva and sinotubular junction). The aim of this study was to visualize and characterize the changes in aortic root dimensions during systole and diastole with ECG-gated multidetector row computed tomography (MDCT). MDCT scans of subjects without aortic root disease were analyzed. Retrospectively, ECG-gated reconstructions at each 10% of the cardiac cycle were made and analyzed during systole (30–40%) and diastole (70–75%). Axial planes were reconstructed at three different levels of the aortic root. At each level the maximal and its perpendicular luminal dimension were measured. The mean dimensions of the total study group (n = 108, mean age 56 ± 13 years) do not show any significant difference between systole and diastole. The individual dimensions vary up to 5 mm. However, the differences range between minus 5 mm (diastolic dimension is greater than systolic dimensions) and 5 mm (vice versa). This variability is independent of gender, age, height and weight. This study demonstrated a significant individual dynamic change in the dimensions of the aortic root. These results are highly unpredictable. Most of the healthy subjects have larger systolic dimensions, however, some do have larger diastolic dimensions.